Jozef Zwierzycki, a prolific Polish geological mapping expert in Indonesia, 1914-1938 - J.T. (Han) van Gorsel; Alina Chrzastek; Anna Gorecka-Nowak (Ikatan Ahli Geologi Indonesia, 2020)
Jozef Zwierzycki was a Polish-German geologist with a very eventful life. This included a long and remarkably productive career with the Dienst van het Mijnwezen (Bureau of Mines/ Geological Survey of the Netherlands Indies) from 1914-1938, first as a field geologist and eventually as Head of the Geological Survey Department. This was followed by an eventful late career back in Poland during and after World War II.Zwierzycki left a legacy of about 50 scientific publications and a series of maps on the geology of the Netherlands Indies. In addition to his publications, he also authored many unpublished reports on surveys on gold, tin, petroleum and coal deposits in various parts of Indonesia.Jozef Zwierzycki was born on 12 March 1888 in Krobi (Kroben), which is now in western Poland, but until 1918 was under Prussian (German) control. He went to elementary school in Krobi and completed high school in Gnesen. From 1908 he studied natural sciences and geology in Leipzig, Munich and Berlin. He obtained a doctorate in geology in October 1913 from the Alexander von Humboldt University in Berlin, with a thesis on ammonites from the 1911-1913 Tendaguru Expedition to Tanganyika, East Africa. This was followed by study at the Bergakademie (Mining Academy) of Berlin, where he graduated as a mining engineer in early 1914.